(untitled) (Research, Society and Development, 2023)
Identifying the species of urban bees, characterizing them and publicizing them is a way of contributing to the preservation of these insects. The present work aimed to identify the species of social bees that inhabit urban and central green areas of Poços de Caldas (Minas Gerais, Brazil) and identify the preferred tree species, determine the height of the nests and record the dynamics of their number among 2018 and 2022. To this end, after active search and data recording, including photography, a digital map was created. Nests of Scaptotrigona bipunctata (the most common), Nannotrigona testaceicornes, Tetragonisca angustula, Plebeia droryana, and Apis mellifera were found. These were found in a few tree species (Tipuana tipu, Jacaranda cuspidifolia, Cunninghamia lanceolata, Araucaria bidwillii, and Taiwania cryptomerioides). Of these, only J. cuspidifolia is endemic to Brazil and the preferred ones were T. tipu and C. lanceolata. S bipunctada was one of the bee species that showed the greatest variation in nest height, contrasting with T. angustula, which prefers to nest below 0.5 m or Apis and T. hyalinata, which prefer to nest at heights greater than 4 m. A decrease in the number of T. angustula bee nests and an increase in A. mellifera nests was noted between the 2018 and 2022 surveys. The presence of native bees in green areas suggests similar spaces can become reservoirs for these species, contributing to their preservation. On the other hand, the simultaneous presence of A. mellifera nests suggests the need to implement different environmental development strategies.